2022
DOI: 10.1371/journal.pone.0271895
|View full text |Cite
|
Sign up to set email alerts
|

Hematological abnormalities before and after initiation of cancer treatment among breast cancer patients attending at the University of Gondar comprehensive specialized hospital cancer treatment center

Abstract: Background Breast cancer is the most frequent and fatal cancer type globally. The fatality rate of breast cancer is mostly due to disease complications like hematological alterations. Therefore, this study aimed to assess the hematological abnormalities before, during, and after the initiation of cancer treatment in breast cancer patients at the University of Gondar comprehensive specialized hospital. Methodology Hematological profiles were collected from 267 breast cancer patients who attended the cancer tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
8
9
0
Order By: Relevance
“…In line with previous study ndings [14,29], signi cant differences in mean MPV, MCV, MCH, and MCHC values were not observed before AC treatment and after the completion of the 3 rd cycle of AC treatment. This indicates that the AC treatment didn't affect all blood cell indices.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In line with previous study ndings [14,29], signi cant differences in mean MPV, MCV, MCH, and MCHC values were not observed before AC treatment and after the completion of the 3 rd cycle of AC treatment. This indicates that the AC treatment didn't affect all blood cell indices.…”
Section: Discussionsupporting
confidence: 92%
“…Contrarily, signi cant differences in monocyte and basophil were not observed between treated and untreated BC patients. This nding is in line with studies conducted previously [13,14]. However, another study [12] showed that a signi cant difference in monocyte and basophil count was observed after 3 rd cycle of AC treatment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations